Let’s Name It: Identifying Cultural, Structural and Extractive Violence in Indigenous and Extractive Industry Relations - Sehlin MacNeil, Kristina (Journal of Northern Studies, 2019)
This article on conflict and power relations between extractive industries and Indigenous groups in Sweden and Australia draws on two case studies to compare situations for Laevas reindeer herding Sami community in Northern Sweden and Adnyamathanha Traditional Owners in South Australia. In this international comparison the analysis, based on the research participants’ narratives, employs Johan Galtung’s concepts of cultural and structural violence as analytical tools to further explore and contrast the participants’ experiences of interactions with extractive industries and industrial proponents. In addition, this study introduces extractive violence—defined as a form of direct violence but relating specifically to extractivism and Indigenous peoples—as a complement to Galtung’s model, known as the violence triangle. The results show that although the expressions of cultural, structural and extractive violence experienced by the two Indigenous communities varied, the impacts were strikingly similar. Both communities identified extractive violence, supported by structural and cultural violence, as threats to the continuation of their entire cultures. The study also shows that in order to address violence against Indigenous peoples, Indigenous and decolonising perspectives must be taken into account.